2019
DOI: 10.3390/sports7050113
|View full text |Cite
|
Sign up to set email alerts
|

Device-Assessed Physical Activity and Sedentary Behaviors in Canadians with Chronic Disease(s): Findings from the Canadian Health Measures Survey

Abstract: Physical activity and sedentary behaviors (SB) are major determinants of quality of life in adults with one or more chronic disease(s). The aim of this study is to compare objectively measured physical activity and SB in a representative sample of Canadian adults with and without chronic disease(s). The Canadian Health Measures Survey (CHMS) (2007–2013) was used in this study. Daily time spent in physical activities and sedentary behaviors were assessed by an accelerometer in Canadians aged 35–79 years. Data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…As a strength, the current study collected self-report data on physical activity companions and objectively measured movement intensity in the daily lives of individuals after stroke and their partners over 14 days. Walking capacity (gait speed) and average MVPA per day in individuals after stroke who participated in our study were comparable to population averages ( 51 , 71 ). Furthermore, the sample was relatively diverse with respect to education and living environments (rural vs. metropolitan).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As a strength, the current study collected self-report data on physical activity companions and objectively measured movement intensity in the daily lives of individuals after stroke and their partners over 14 days. Walking capacity (gait speed) and average MVPA per day in individuals after stroke who participated in our study were comparable to population averages ( 51 , 71 ). Furthermore, the sample was relatively diverse with respect to education and living environments (rural vs. metropolitan).…”
Section: Discussionsupporting
confidence: 67%
“… 1 This number compares to average MVPA per day as measured by accelerometer for Canadian adults living with a chronic disease [15.6 min/day; ( 51 )]. …”
mentioning
confidence: 99%
“…Although challenged by the lack of available evidence, higher levels of daily MVPA and LPA and lower levels of SB were found than previously reported in people with multimorbidity. In a Canadian cohort study, Hains-Monfette et al [ 57 ] reported that people with two chronic conditions performed a daily average of 10 minutes of MVPA, 171 minutes of LPA and 580 minutes of SB. These results were based on an adult population with somewhat similar chronic conditions (heart disease, diabetes, and cancer and/or COPD) to the ones included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that physical diseases were associated to less daily time spent in PA Hains-Monfette et al, 2019).…”
Section: Preprint -Non Peer Reviewedmentioning
confidence: 99%